Ecological Sin and Its Impact on Environmental Crisis: A Case Study of Landslides and Floods in Kali Village, Minahasa - Riedel Christian Gosal; Peggy Sandra Tewu; Olga Neltje Komaling (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study investigates the interconnection between ecological sin and environmental crisis in Kali Village, Minahasa, where recurring landslides and flooding are symptoms of deeper moral, spiritual, and structural failures. Despite the growing environmental degradation driven by deforestation, unsustainable land conversion, and waste mismanagement, community and ecclesial awareness of ecological responsibility remains limited. Drawing on qualitative case study methods, the research employed in-depth interviews, focus group discussions, field observations, and document analysis with 30 participants, including church leaders, congregants, local residents, and environmental activists. Thematic analysis revealed that environmental destruction is not merely a technical issue but a manifestation of extractive capitalism, weak local governance, and disconnection between Christian doctrine and ecological practice. While the Church holds significant moral authority, its response has largely been charitable and reactive, failing to address systemic injustices or integrate ecological sin into theological teaching. Many congregants perceive environmental harm as an economic necessity rather than a spiritual transgression, reflecting their fragmented understanding of stewardship. The study further identifies a critical gap between the church’s potential as a transformative agent and its current inaction, particularly in advocating policy change or empowering communities through ecological education. The findings underscore that ecological degradation is inseparable from social injustice, where vulnerable groups bear the brunt of decisions made by external actors and indifferent institutions. The research concludes that a theological reframing is urgently needed one that redefines the church’s mission as intrinsically ecological. To be credible, the church must move beyond symbolic stewardship and embrace a prophetic and participatory role in environmental restoration, grounding its mission in justice, accountability, and creation care.